Digital Comic Development to Improve Life Skills in Early Children - Aini Indriasih (Universitas PGRI Adi Buana Surabaya, 2023)
This research aims to develop digital comics as a learning medium to improve early childhood life skills. The approach used is research and development, with the mixed methods design, between qualitative and quantitative methods used in an integrated and complementary manner. The subjects in this study were kindergarten students at Batik Kindergarten, Kudus district. The collection techniques used were questionnaires, observations, interviews, and documentation. Digital comics developed refers to the development stages carried out by Borg and Gall, which consist of four stages: a preliminary study, development, field testing, and product dissemination and socialization. Digital comic learning media can be applied in learning to improve early childhood life skills. Quantitatively, the assessment of material experts is (3.87) in the excellent category. Expert's review is based on the suitability of the curriculum, the truth of the content and the method of presenting the material are included in the excellent category). The media expert's assessment obtained a score of (4.0) the media expert's review is based on considerations of production, visual design, and technical quality, with a score of (4.0) in the excellent category. While the assessment given by students at the field test stage (3.88), the field test is broader (3.99), and the operational test (3.91), the score shows that digital comic learning media is categorized as good, which means that digital comic learning media is effectively used to improve early childhood life skills. Qualitatively, digital comic media as a learning medium to enhance life skills can attract students' attention to learning, facilitate student learning, and stimulate students to remember the material more easily.